(3efgGL GdHjGf ajeG jSJYedg GdEfSGfs - (3jMji Hf YjSi Hf LRdI GdHZOGOj, CHh Ydj,J (B493 (3g` s
(3ChdgG (B:s
(3Edi PcQ cd TF ai HGHg cGdMTGFT hGdMHhH hGdChQGb hGdKeGQ hGdYUGQGJ s
(3BNQgG (B:s
(3hjbdY GdHhGSjQ hjSgd GdHdZe hGdCNdGW GdZdjXI s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B161 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B218s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1870s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
Keywords: (3GdWHs